AVALIAÇÃO DE IMPACTOS AMBIENTAIS DA SOJICULTURA EM UM ECOSSISTEMA AQUÁTICO DA MICRORREGIÃO DE CHAPADINHA, MA - Presoti, Antonio Eduardo Pinheiro (2008)
EVALUATION OF ENVIRONMENTAL IMPACTS OF SOJICULTURA IN AN AQUATIC ECOSYSTEM OF MICRO-REGION OF CHAPADINHA, MA. The studies were accomplished in in the micronbasin of the Rio Preto, affluent for the right side of the basin of the Rio Munim. The Rio Preto is born to the south of the city of Buriti, coordinated: 3°56' 41.96" South and 43° 2' 31.40" West. After to cover about 230 km, empties in the Rio Munim, in the locality of Nina Rodrigues. The Rio Preto bathes the following cities: Buriti, Brejo, Milagres do Maranhão, Anapurus, Mata Roma, Urbano Santos, Chapadinha, São Benedito do Rio Preto and Nina Rodrigues. It is a predominantly agricultural region, where the agricultural activities come if intensifying in recent years. The cities of Buriti, Anapurus, Mata Roma and Brejo, come developing an intensive agriculture, with prominence for the soya cultivation. With intention to know the levels of contamination of pesticides in the high course of the Rio Preto, proceeding from the soybean cultivation and implications of these contaminations of pesticides in the phytoplankton community four campaigns of sampling in three points had been carried through show: Rio Preto - RP2 - latitude 3°51' 47,70" S and longitude 43° 02' 46,14" , Rio Preto - RP3 - latitude 3°43' 19,98" S and longitude 43°00' 40,32" and the Rio Preto - RP4 - latitude 3°31' 34,98" S and longitude 43°02' 53,46" . These campaigns of sampling are carried through at the beginning of december of 2007, final of january, end of march and beginning of june of 2008, considering the two first campaigns carried through in the period of dry season and the two subsequent ones in the rainy period. The dates of the campaigns had also aimed at to follow the cycle of plantation of the soya crop, that starts in the half of january and ends in the half of June, with a tolerance of days for the beginning and end of the cycle. They had been registered in situ given on the temperature of air and water, concomitantly collected water samples the 20 cm of the surface for analysis of variable (pH, dissolved oxygen - OD, electric conductivity, solids total, turbidez, nitrogen under the form nitrate, phosforus under the form fosfate); biological (phytoplankton density and the diversity and eqüitability, wealth indices; it analyzes of pesticides (alaclor, aldrin, 2,4-D, 2,4,5-T, carbofuran, clorpirifós, clorpirifós-oxon, carbendazim, cipermetrina, monocrotofós, metamidofós, paraquate, thiram and carbofuran). In the four campaigns of sampling, in the three sampling points, therefore, of the twelve taking of samples, they had been detected presence of pesticides in eleven of the taking. In terms of number of pesticides, of the thirteen investigated, they had been detected eight presence. Also detected the presence of organoclorate product - aldrin, forbidden the use, in Brazil, for Portaria Anvisa nº 329/85. The studies had shown a correlation enter the level of contamination of pesticides and the impact caused for the increase of the phytoplankton frame number in amostral point RP2. Amongst the species of phytoplankton, Oocystis lacustris it was the species that presented a bigger number of individuals in relation to the other species. The presence of the pesticides and the alterations in populations of phytoplankton species had come to prove, thus, the ambient impacts proceeding from the farm soy activities in the region.